Double spiral detection channel for on-chip chemiluminescence detection - Lok, Khoi Seng (2012)
In this paper, we introduced a three-layered microchip that consists of a double spiral channel design for chemiluminescence (CL) detection and a passive micromixer to facilitate the mixing of reagents. The design with two overlapping spiral channels doubled the CL intensity emitted from the reaction as compared to the design with a single spiral channel. The addition of the passive micromixer improved the signal by 1.5 times. Luminol-based chemiluminescence reaction was used for the characterization of the device. This microchip was successfully tested with the determination of L-cysteine and uric acid.